A Rat in a Maze: Analysis of Violation and Flouting Of Maxims in the Television Adaptation of Margaret Atwood’s The Handmaid’s Tale - Vicente Mari Mangilaya II (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2020)
The influential work of H.P. Grice (1975) on Cooperative Principle has been extensively applied in both authentic and fictional contexts. Scholars in the field of pragmatics argued that non-observance of maxims lead into the creation of humor (Khosravizadeh and Sadehvandi, 2011; Jorfi and Dowlatabadi, 2015; Zeb, 2019; Kuang and Zhao, 2017) and character development (Pertiwi , 2013; Saradifa, 2020; Sembiring and Ghozalo, 2017). Built on this argument, the present study was conducted to confirm such claim by focusing on the instances of violating and flouting of maxims and the purpose it served in an intertwined context of reality and fiction in the television adaptation of Margaret Atwood’s The Handmaid’s Tale. Findings revealed that characters deliberately violated and flouted the maxims in order to avoid conflict and to also highlight information, which are deemed indispensable in building the narrative. This study also found instances of violation and flouting of maxims as a product of suppression of women characters that mirror gender inequalities in many parts of the globe.